Valores geneticos de caracteres productivos y reproductivos en bovinos Romosinuano - Oáa, G.A.=700 1 Perez, J.E.; Suarez, M.A.
(En, Es)
ilus., 19 ref.
Keywords: GANADO BOVINO; RAZAS INDIGENAS; VALOR GENETICO; PROGENIE; CRECIMIENTO; REPRODUCCION; COLOMBIA; ROMOSINUANO; CORPOICA